Pengaruh Kemampuan Hafalan Al-Qur’an Terhadap Kemampuan Matematika - Tasya Nurhayati; Nurul Azizah Pasaribu; Reska Oktaviola; Dea Wullan Dari; M. Imamuddin (KOLONI, 2023)
The effect of Qur'anic memorization on mathematical ability is an interesting topic to research because the two fields of study are very different in terms of materials and learning methods. On the one hand, Qur'anic memorization emphasizes memorization of holy verses and continuous repetition, while on the other hand, mathematics teaches concepts and problem solving through logical reasoning and analytical skills.SLR (Systematic Literature Review) research method in which the researcher collected as many as 20 journals related to the title of this study. The research results of the journal literature review are: a) concluded that the ability to memorize the Qur'an is very influential or has a significant influence on students' mathematical abilities such as on students' mathematics learning outcomes, students' mathematical problem solving, and students' mathematical thinking skills b) there is a positive and substantial influence between memorizing the Qur'an on students' mathematical, logical and emotional intelligence c) the ability to memorize the Qur'an is in a strong enough category to influence students' mathematical abilities. Based on the results of the researcher's analysis of the research subjects consisting of 20 journals related to the title of this study, it can be concluded that research is more likely to use quantitative methods, namely as much as 75% and more implemented in junior high schools / equivalent, namely as much as 43% and based on the results of research from 20 journals that were used as research subjects explained that the ability to memorize the Qur'an greatly affects a person's mathematical abilities which in this study almost all journals discuss the effect of memorizing the Qur'an on students' mathematical abilities which include mathematics learning achievement, the ability to understand mathematical concepts, the ability to reason mathematically and also the ability to think critically and only one journal discusses the effect of the ability to memorize the Qur'an on students' mathematical abilities. Keywords: Memorize al-Qur’an, Matematics Learning Outcame, and math ability.